Synergizing Immunostimulants and Ecology for Sustainable Tropical Aquaculture Management - Yuniwati, Eny Dyah; Shumaila, Shumaila (CV. Bimbingan Belajar Assyfa, 2024)
The rapid intensification of tropical aquaculture production presents formidable challenges in balancing disease management with environmental sustainability. Shifting from traditional antibiotic reliance, this review delves into the ecological integration of immunostimulants within aquaculture systems. By examining recent advancements in disease management, we assess how immunostimulants harmonize with ecosystem dynamics to bolster environmental resilience. Employing ecological systems theory, our framework incorporates artificial intelligence-enhanced monitoring and biosecurity strategies, proposing a holistic model for disease prevention. Our findings reveal that integrating immunostimulants with advanced ecological practices—such as polyculture systems and biofloc technology—yields synergistic benefits, enhancing fish immunity and ecosystem vitality. Specifically, this integrated approach achieves a 45% reduction in disease incidence compared to conventional methods, while also improving water quality and fostering beneficial microbial communities. The results underscore that the future of sustainable aquaculture hinges on sophisticated integration of immunostimulants within broader ecological management, supported by innovative technologies and comprehensive environmental monitoring. This approach not only addresses disease challenges but also promotes a more resilient aquaculture environment.